DAMPAK PERANG ISRAEL-HAMAS TERHADAP HARGA SAHAM DAN MINAT BELI MASYARAKAT PRODUK PENDUKUNG ISRAEL - Rahmani, Annisa Nadiyah (Academy of Education Journal, 2023)
The Israel-Hamas war became a public concern because of acts of violence and genocide in Palestine, public criticism paid special attention to share prices and people’s interest in purchasing products supporting Israel. The research here aims to determine the decline in stock prices before the Israeli military aggression and after the military aggression, namely on September 1, 2023 and November 1, 2023. The research uses mixed methods because consists of quantitative and qualitative. Researchers used quantitative methods selected 30 companies from America, France, Germany, France, England and Switzerland whose products are popularly used by Indonesian people and competitors for local Indonesian products. The qualitative method was measured by distributing questionnaires using Google Form which is 60 selected respondents from generation Z and the Millennial generation in the city of Bandung by aged 25-35. The research results show that the Israel-Hamas war had an impact on decreasing stock prices. The Israel-Hamas war has an impact on interest in purchasing products who’s supporting Israel.